Democratizing the Production of Interactive Hardware - Hodges, Steve (UIST 2020, 2020)
The development of new hardware can be split into two phases: prototyping and production. A wide variety of tools and techniques have empowered people to build prototypes during the first phase, but the transition to production is still complex, costly and prone to failure. This means the second phase often requires an up-front commitment to large volume production in order to be viable. I believe that new tools and techniques can democratize hardware production. Imagine “DevOps for hardware” – everything from circuit simulation tools to re-usable hardware test jig designs; and from test-driven development for hardware to telepresence for remote factory visits. Supporting low volume production and organic scaling in this way would spur innovation and increase consumer choice. I encourage the UIST community to join me in pursuit of this vision.